An evidence‐based structured one‐year programme to sustain physical activity in patients with heart failure in primary care: A non‐randomized longitudinal feasibility study - Lena Nordgren (Nursing Open, 2020)
Abstract Aim The primary objective of this non‐randomized feasibility study was to test a 1‐year model programme for sustaining/increasing patients’ motivation to perform daily physical activity. Design Non‐randomized longitudinal feasibility study with a one‐group repeated measures design. Methods The study took place at a primary care centre in mid‐Sweden in 2017–2018. The model programme included individual and group‐based support, individualized physical activity prescriptions, a wrist‐worn activity tracker and an activity diary. The main outcomes were the participants’ perceptions of programme feasibility and scores on the Exercise Self‐Efficacy Scale. Results Seven patients were recruited. Six patients completed the programme that was perceived to imply learning, motivation and support. Compared with baseline, the median score of the Exercise Self‐Efficacy Scale improved 3 months after participants completed the programme.